2018
DOI: 10.1016/j.esxm.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Validation of a German Version of the Sexual Complaints Screener for Women in a Female Population Sample

Abstract: BackgroundTo date, neither the original English nor any of the translated versions of the Sexual Complaints Screener for Women (SCS-W) have been tested for their psychometric properties.AimTo evaluate the validity and utility of the German version of the SCS-W by assessing content, convergent, and discriminant validity.MethodsA population sample of 309 women (mean age = 26.9 years) completed the online survey and had matching data available on the SCS-W and the Female Sexual Function Index (FSFI). Spearman biv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…One of the possible reasons could have been the FSFI's lack of differentiation between the pain experienced due to penile-vaginal penetration and difficulties allowing vaginal penetration to occur. The correlation coefficient between the SCS-W pain domain and the FSFI pain domain was higher than .30 which was consistent with the results of Burri and Porst's research [14]. The inconsistency mentioned was expected since there the FSFI did not constitute of items that specifically evaluated vaginismus.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…One of the possible reasons could have been the FSFI's lack of differentiation between the pain experienced due to penile-vaginal penetration and difficulties allowing vaginal penetration to occur. The correlation coefficient between the SCS-W pain domain and the FSFI pain domain was higher than .30 which was consistent with the results of Burri and Porst's research [14]. The inconsistency mentioned was expected since there the FSFI did not constitute of items that specifically evaluated vaginismus.…”
Section: Discussionsupporting
confidence: 89%
“…The SCS-W has only been tested for its validation in German so far [14]. The current study aims to evaluate the SCS-W for its validity and reliability in the Turkish language.…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy is that 5 studies showed support for a 6-factor structure, 16,65,75,82,85 whereas 11 studies showed support for a 5-factor structure with a merging of the desire and arousal subscales. 2,20,24,33,38,50,58,63,82,92,93 1 study showed support for a 5-factor structure with a different merging of subscales, 39 and 7 studies showed support for <5 factors. 27,41,45,73,82e84 1 study used item response theory analysis and was rated indeterminate because no fit measures were reported.…”
Section: Structural Validitymentioning
confidence: 93%
“…To assess the test-retest reliability of the U-UDI and the FSFI in women with MS Bornefeld-Ettmann et al 23 German-speaking women 465 The German translation of the SSEI-SF by Zeanah and Schwarz (1996) was validated via an online survey with 557 women and then investigated in a clinical sample of women suffering from PTSD after sexual and physical abuse compared with healthy controls Burri et al 24 Sexually active Swiss women 309 To evaluate the validity and utility of the German version of the SCS-W by assessing content, convergent, and discriminant validity Carpenter et al 25 Midlife postmenopausal women 93 To evaluate whether a single item from the FSDS-R could be identified to use to screen midlife women for bothersome diminution in sexual function Carpenter et al 26 Peri-and postmenopausal women reporting hot flashes…”
Section: 966mentioning
confidence: 99%
“…The German version of the scale was recently validated. 15 Along with the SCS-W, the Orgasm subscale of the German version of the Female Sexual Function Index (FSFI) was also used. 16,17 The FSFI is a 19-item measure that allows a multidimensional assessment of women's sexual response.…”
Section: Sex and Orgasm-related Variablesmentioning
confidence: 99%